Edukacja włączająca z perspektywy szkoły specjalnej na przykładzie doświadczeń specjalistycznych centrów wspierających edukację włączającą (SCWEW) = Inclusive education from the perspective of a special school on the example of the experience of Specialized Support Centers for Inclusive Education (SCWEW) - Flanczewska-Wolny, Maria; Wolny, Jakub (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The idea of inclusive education, which development we have been observing since the turn of the 20th and 21st centuries in the world, is commonly perceived as "the most serious way of progress in special pedagogy and special education today, as well as an important vision of school reform" (Szumski 2014: 127). However, this is not a simple process, it requires long-term and comprehensive activities aimed at building readiness for mutual coexistence both on the part of the environment of people with disabilities and the community of fully able people, "the need to prepare able-bodied people and people with disabilities to establish, develop and maintain mutual relations" (Dyrżałowska 2018: 15), which are the essence of inclusion. However, are Polish schools ready for such a change? Are they ready to provide individualized support for each student who needs it, as well as to implementpractical inclusive solutions? Are teachers themselves ready to verify their own attitudes and ways of thinking, change their teaching strategies or assessments methodologies of their students?
Keywords: inkluzja; edukacja włączająca; szkoła specjalna; Specjalistyczne Centrum Wspierania Edukacji Włączającej (SCWEW); Inclusion; inclusive education; special school; Specialized Center Supporting Inclusive Education (SCWEW)